THE EFFECT OF NASTY AND NON-NASTY MARRIED CELEBRITY ENDORSERS ON THE ATTITUDE, BRAND, AND PURCHASING INTENTION OF THE CONSUMER - Lina, Lina (Journal of Indonesian Economy and Business, 2009)
This research describes how Advertising Response Modelling (ARM) provides aÂ framework to measure advertising performance by integrating several multiple measuresused in copy research. Several studies found that the use of celebrity endorsers is aÂ popular execution device, but it is not without risk. The author reports the study examininghow the case of negative information about an endorser can affect three variables: attitudeÂ toward ads, attitude toward brand, and purchasing intention. The aims of this researchwere to measure the influence of negative traits of endorsers on consumersâ attitudeÂ toward the product, the brand, and the purchasing intention. Experimental research designÂ was employed in this study. The participants in this research were students who areÂ studying at Master of Economics Science, Gadjah Mada University, Yogyakarta. ThereÂ were 100 participants out of 113 samples used as participants. Those participants wereÂ exposed to a printed advertisement of drinking product âExtra O2â brand. Then, theyÂ were also exposed to the case of negative information of the endorsers who have and haveÂ no nasty married. After that, the participants were asked to fill in self-administered andÂ structured questionnaire. By using ARM and One-way ANOVA analysis, the researchÂ shows that endorsers without divorce problem has influenced positively the audience morethan that of endorser with nasty married. However, there are no significant differencesÂ between men and women in responding the advertising with nasty and non-nasty marriedendorsers.Â Keywords: Advertising Response Modelling (ARM), endorsers with nasty and withoutÂ nasty married Attitude toward ads, attitude toward brand, and purchasingÂ intention.